2020
DOI: 10.3390/su12187769
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality Effect Analysis and Recognition of Charging Behaviors of Electric Vehicles: A Data Science Approach

Abstract: Electric vehicles (EVs) presence in the power grid can bring about pivotal concerns regarding their energy requirements. EVs charging behaviors can be affected by several aspects including socio-economics, psychological, seasonal among others. This work proposes a case study to analyze seasonal effects on charging patterns, using a public real-world based dataset that contains information from the aggregated load of the total charging stations of Boulder, Colorado. Our approach targets to forecast and recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…RF is an ensemble method that relies on multiple decision trees. According to [64], several studies have revealed that RF can produce more stable and accurate results than SVMs in load prediction, indicating its effectiveness in forecasting electrical load. In general, SL algorithms can be applied to EV charging, from learning of instances to predicting optimal charging schedules.…”
Section: A a Revisit Of ML Techniques And Their Applicability To Ev C...mentioning
confidence: 99%
“…RF is an ensemble method that relies on multiple decision trees. According to [64], several studies have revealed that RF can produce more stable and accurate results than SVMs in load prediction, indicating its effectiveness in forecasting electrical load. In general, SL algorithms can be applied to EV charging, from learning of instances to predicting optimal charging schedules.…”
Section: A a Revisit Of ML Techniques And Their Applicability To Ev C...mentioning
confidence: 99%
“…The basic parameters usually considered to develop a simulation model of a battery are the capacity , voltage , current , temperature , state of charge , load and internal resistance , to mention a few (Acharya et al, 2019). Notice that, among the various configurable parameters of the above mathematical models, the capacity, , is usually considered of particular interest for its ability to drive the battery behaviour and being associated to its degradation (Dominguez-Jimenez et al, 2020). For such reasons, in this work, the capacity, , is the parameter to be calibrated by the proposed approach.…”
Section: Earth Observation Satellite Batterymentioning
confidence: 99%
“…Finally, from the point of view of new applications and upright ideas that can be carried out thanks to PV power systems, in this Special Issue has published papers related to the pumping in urban water pressurized networks, nano-grids to road lighting systems, charging of electric vehicles, and virtual power plants (Contributions [14][15][16][17]. All the contributions in this collection of articles consider solutions to current problems that are worth revising.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%